2002
DOI: 10.1067/mva.2002.121746
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response in the acute phase of deep vein thrombosis

Abstract: Our data show an apparent inflammatory response with highest measured concentrations of inflammatory markers on the day of admission and a subsequent decrease during the next days. This response supports the hypothesis that elevated inflammatory markers are a result rather than a cause of venous thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
121
1
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 19 publications
4
121
1
6
Order By: Relevance
“…Increased levels of serum C-reactive protein (CRP), a marker of systemic inflammation, have been reported in patients with venous thrombosis and PE (Roumen-Klappe et al, 2002). The CRP assay is cheap and readily available 24 h a day in most hospitals.…”
mentioning
confidence: 99%
“…Increased levels of serum C-reactive protein (CRP), a marker of systemic inflammation, have been reported in patients with venous thrombosis and PE (Roumen-Klappe et al, 2002). The CRP assay is cheap and readily available 24 h a day in most hospitals.…”
mentioning
confidence: 99%
“…Follow-up studies of patients with DVT who were treated with anticoagulants have shown that in many cases only partial clearance of the thrombus occurs. [29][30][31][32] Damage to venous valves leading to valvular reflux occurs frequently after DVT, probably by thrombus-induced activation of inflammation, fibrous scarring associated with acute and resolving thrombosis, or venous dilation distal to the obstructed venous segment [33][34][35][36] (Figure 2). Of the 2 mechanisms, persistent venous obstruction appears to be the more important; on the basis of 2 recent reports, the presence of residual venous obstruction 6 months after DVT alone or in combination with venous reflux predicted the development of PTS, whereas the presence of venous reflux alone did not.…”
mentioning
confidence: 99%
“…Es en este punto donde los reactantes de fase aguda y los marcadores de inflamación podrían desempeñar un papel importante. Es bien conocido que la inflamación crónica es un factor de riesgo para la ateroesclerosis y que la elevación de los marcadores de inflamación están asociados a eventos coronarios (2). Esta relación está menos demostrada en la ETEV.…”
Section: Abstract Objective: To Assess the Association Of Acute Reactunclassified